El códice como entidad unitaria : apuntes para la edición crítica del manuscrito 431 de la Biblioteca Nacional de Madrid (Estudios de Historia de España, 2016)
The manuscript 431 of the National Library of Madrid was composed around 1360, in the heat of the Civil War that pitted Pedro I and Henry II. This codex composed in the mid-fourteenth century is one of the greatest testimonies of an attempt to formalize seigneurial law Castilla never officially established. The texts contained therein were never considered as a unit and therefore were always edited and studied separately. The paper aims to identify formal guidelines that establish the unitary entity based not only on its physical aspects (fonts, materials, language, etc.) but also on internal lines of signifi cance at both syntagmatic (contiguity relations in praesentia) and the paradigmatic aspects (associations organizing reading patterns).
Keywords: Ecdotics; Manuscript Culture; Historicity; Semiotics